2010
DOI: 10.1016/j.ejcts.2010.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Early failure of xenogenous de-cellularised pulmonary valve conduits — a word of caution!☆

Abstract: On the basis of our short-term results, the Matrix P plus de-cellularised tissue-engineered pulmonary valve cannot be regarded as an ideal conduit for right ventricular outflow tract reconstruction, as the widespread use of these grafts may increase the possibility of frequent early conduit failures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 24 publications
4
68
0
1
Order By: Relevance
“…Currently available acellular xenogeneic pulmonary heart valve scaffolds have shown clinical outcomes [17][18][19][20] that have indicated the need for the development of acellular valved conduits that are devoid of cells, DNA and residual a-gal. To the authors' knowledge, this is the first study that has assessed the total DNA and the presence of a-gal in all regions (leaflets, pulmonary wall, myocardium, and leaflet connection) of an acellular porcine pulmonary root conduit.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently available acellular xenogeneic pulmonary heart valve scaffolds have shown clinical outcomes [17][18][19][20] that have indicated the need for the development of acellular valved conduits that are devoid of cells, DNA and residual a-gal. To the authors' knowledge, this is the first study that has assessed the total DNA and the presence of a-gal in all regions (leaflets, pulmonary wall, myocardium, and leaflet connection) of an acellular porcine pulmonary root conduit.…”
Section: Figmentioning
confidence: 99%
“…A number of other studies later reported inflammatory responses to the Matrix PÔ porcine pulmonary grafts associated with peripheral conduit narrowing. 17,19 It was also reported that the Matrix PÔ Plus valve displayed early obstruction following implantation in pediatric patients. 20 It is likely that these problems were due to the glutaraldehyde fixed pericardial patches used in the grafts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been described for use in repair of rotator cuff defects [59,60], as well as for the treatment of diabetic foot ulcers [61]. Finally patch of EP tissue were applied either for the coverage [17] or for the self-made manufacture of heart valves substitutes [62]. Like many of the xenogeneic tissues intended for clinical use, even the EP patches are supplied after GLU fixation.…”
Section: Equine Pericardiummentioning
confidence: 99%
“…Scaffolds derived from mammalian tissues have been used to repair or replace a variety of damaged or diseased tissues including cardiac [1,2], esophageal [3,4], dermal [5], musculotendinous [6,7] and ocular [8], among others. Results of preclinical and clinical studies have varied from success [9][10][11] to complete failure [12][13][14][15][16][17]. The host response to these materials can depend on several aspects such as the original species (e.g.…”
Section: Introductionmentioning
confidence: 99%